Wood Specific Gravity of Temperate Forest Species of Garhwal Himalaya, India - Mahato, Subhasis; Iqbal, Kaiser; Aziem, Showkat; Hussain, Aatif; Dharmveer; Dasgupta, Sabyasachi; Todaria, N. P. (Indian Forester, 2019)
One of the parameters for terrestrial biomass estimation is specific gravity of the woody species. Present study reports wood specific gravity of 26 species. Maximum moisture content method was used to calculate specific gravity. Specific gravity of eight species (8) was found between 0.71 - 0.80, seven species between (0.61 - 0.70) and specific gravity of 0.31 - 0.40 was recorded for only one species. Out of 26 species, Cedrus deodara has the highest specific gravity and the lowest value was recorded for Rubus ellipticus.